Learners Management by Segregation Gender-Based - Chotimah, Chusnul (Martabat: Jurnal Perempuan dan Anak, 2020)
A general assumption states that if a management is implemented by gender segregation policy, it will be biased or experience inequality, moreover, if this bias is implemented in such educational institutions. It is worried that there will be gender discrimination in education atmosphere which is contrary to Indonesian Law no. 7 of 1984 regarding to the elimination of all forms of discrimination against women (CEDAW), Law no. 25 of 2000 concerning to National Development Program (PROPENAS) in improving the quality of women, and also contrary to the concept of Islam itself which never differentiates between men and women except for the level of devotion. However, this negative assumption is not fully proven. In fact, MA Darul Hikmah as a boarding school-based Islamic education institution that implements gender segregation remains a reference among society. What arguments do the parents’ have? How is the implementation of gender segregation management, and what are the implications? Those are what this article studies. The data of the current study was gained by conducting some interview with Islamic Elders, educators, teachers (ustaz), students (santri), and parents, supported by documentation and observations that have been analyzed using Milles and Hubberman’s theory. By then, the following results are obtained: 1) The reasons for the application of learners management by using gender segregation-based are, maintaining the tradition of pesantren inheritance, upholding religious doctrine, and optimizing the roles and achievements of learners; 2) The implementation of gender segregation neither is based on educational discrimination between men and women, nor an obstacle to the implementation of learning, but this can actually create creativity when the learners are provided the same rights, access, roles and participation (balancing management). Gender balancing policies become the supporter of gender responsive management; 3) By gender segregation, it is actually able to provide positive values for learners in terms of building the characters and preventing promiscuity. Meanwhile, the negative impact is, it leads to create awkward interactions between both male and female learners and also able to decrease the motivation to learn.